MENEGOSIASIKAN KEIMANAN DI DUNIA DIGITAL: STUDI PSIKOLOGI KEBERAGAMAAN PADA GENERASI Z - Reza Maulana Dalimunthe; Surawan Surawan (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
The development of digital technology has reshaped the way generation Z constructs and expresses their religious identity. This study aims to explore the psychological dynamics behind the process of negotiating faith that occurs in the digital context among generation Z. Using a qualitative approach with in-depth interviews with a number of informants aged 18–23 years, this study highlights how social media, information algorithms, and online communities influence individuals' understanding, practice, and spiritual meaning. The results show that generation Z tends to experience ambivalence in their religiosity on the one hand, open to pluralism, but on the other hand also exposed to religious polarization. The process of negotiating faith occurs through a complex internal dialogue between traditional values and digital narratives that are often contradictory. These findings contribute to the understanding of the psychology of religiosity in the digital landscape and the importance of the role of digital spiritual literacy in forming a healthy and reflective religious identity.